Report of multiple high-grade gliomas in two patients with shared retained ATRX, wild-type IDH, losses of CDKN2A genes and alterations in the PTEN–PI3K axis. Issue 3 (30th March 2023) - Khatchadourian, Christopher; Guo, Jin; Prasad, Chaya J; Orlando, Robert A; Parsa, Cyrus
Abstract: Solitary gliomas have been well described in the literature. Multiple gliomas, however, have not received the same notoriety, and as such further studies may be helpful in elucidating their unique clinicopathologic features and molecular basis. We present two patients, each with multiple high-grade gliomas, and describe their clinicopathologic and molecular characteristics in comparison with those reported in the literature in an attempt to better understand their shared tumorigenic mechanisms. Extensive molecular, FISH and genomic profiling studies detected multiple unique abnormalities in our two cases with shared molecular features of retained ATRX, wild-type IDH, losses of CDKN2A genes and alterations in the PTEN–PI3K Axis.